ФОЛКЛОРНИ НАРАТИВНИ ТЕОРИИ И НОВИ ПРАКТИКИ (Filološke studije, 2019)
In order to find the distinctive characteristics in Slavic and WestEuropean / American folkloristics, the paper analyzes their relationship in continuity. The further explication is based on discovering the other conceptual differences, in order to get a representation of the contemporary state in the international folklore narrative researches.